2008
DOI: 10.2460/ajvr.69.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body position on intraocular pressure in dogs without glaucoma

Abstract: Body position affects IOP in dogs. When IOP is measured in dogs, body position should be recorded and consistent among repeat evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 16 publications
1
29
3
2
Order By: Relevance
“…In other studies, IOP increases in a range of species were observed with jugular compression. [23-25] Thus, manual restraint method should be reported and carefully considered when interpreting IOP data in red-eared slider turtles, and rostral head or no manual restraint are preferred, due to the lack of significant effect on IOP. In addition, head and body position was shown to impact IOP in a range of species,[11, 23, 26] but both were consistent across groups in our study as turtles were consistently supported with their head and body in a horizontal position during all restraint methods evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, IOP increases in a range of species were observed with jugular compression. [23-25] Thus, manual restraint method should be reported and carefully considered when interpreting IOP data in red-eared slider turtles, and rostral head or no manual restraint are preferred, due to the lack of significant effect on IOP. In addition, head and body position was shown to impact IOP in a range of species,[11, 23, 26] but both were consistent across groups in our study as turtles were consistently supported with their head and body in a horizontal position during all restraint methods evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…5,11,26,31,35 Proposed physiologic mechanisms for this relationship include changes in episcleral venous pressure, ophthalmic arterial pressure, and gravitational pull on blood. 7,27,29 In American flamingos mean IOP by rebound tonometry was significantly higher with the head down in a feeding posture compared with the head upright in a standing posture. 35 A study in raptor species compared median IOP in upright and dorsally recumbent postures.…”
Section: Species (P) a Study In Black-footed Penguins Reported Iop Mmentioning
confidence: 93%
“…The authors proposed acclimatization as the reason for this finding. 7 It is possible that the difference in IOP pre-and postexamination in the macaroni population reflects a similar process of acclimatization.…”
Section: Species (P) a Study In Black-footed Penguins Reported Iop Mmentioning
confidence: 98%
“…Ideally, the animal should be resting quietly and its head should be the same distance above the heart at each interval. 39 Resisting application of the tonometer by nervous or excited dogs, or dogs that are moving, often results in inaccurate readings and may cause the clinician to believe that increased IOP is present when in fact it is absent. In stressed or uncooperative animals, these errors can be very large.…”
Section: Techniques That Evaluate Intraocular Pressurementioning
confidence: 99%